In vitro evidence of the antitumor capacity of Solanaceae and Cucurbitaceae in colon cancer: A systematic review. Issue 23 (15th August 2022) - Mesas, Cristina; Fuel, Marco; Martínez, Rosario; Prados, Jose; Melguizo, Consolación; Porres, Jesús M.
Abstract: Colon cancer is the fourth leading cause of cancer deaths around the world. Despite advances in understanding its etiology and in diagnosis and treatment, new therapeutic strategies are still required. In this sense, the Solanaceae and Cucurbitaceae families have been widely used to treat various pathologies, including cancer, for their bioactive components. The objective of this systematic review was to analyze the antitumor activity of the bioactive components present in extracts from Solanaceae and Cucurbitaceae families using different in in vitro models of colon cancer. 241 publications have been identified (published from January 2008 to January 2020) from different electronic data base. 44 articles were included, 26 of which examined the Solanaceae family. The antitumor activity exhibited by this family was due to the withanolide-type steroid compounds they harbor. 18 articles were related to the Cucurbitaceae family. This family is characterized by their production of cucurbitacin-type triterpenoid compounds and their derivatives, which confer antitumor activity. In conclusion, the different genera belonging to both families are an important source of bioactive compounds with relevant activity against colon cancer. More experimental and in vivo studies will be required to corroborate their antitumor activity and to leverage them in future clinical practice.